스포츠를 통한 기업의 사회적 책임활동과 기업 및 소비자요인의 관계분석 - 김민철; Min Cheol Kim (Ch'eyuk kwahak yŏn'gu, 2012)
이 연구는 스포츠를 통한 기업의 사회적 책임활동이 기업능력, 기업신뢰, 기업평판의 기업요인을 거쳐 고객 만족 및 구매의도의 소비자요인에 어떠한 영향을 미치고 있는가를 분석하는데 연구의 목적이 있다. 이 연구의 조사대상은 G광역시와 J도의 Y시, S시에 거주하고 있는 20세 이상의 생활체육교실에 참가하고 있는 일반시민을 대상으로 하였으며, 연구결과의 도출을 위한 통계처리방법으로는 AMOS 5.0을 활용한 구조방정식 모형 분석 (structural equation model)이 사용되었다. 이에 최종적으로는 276부의 설문지가 분석에 활용되었으며, 다음과 같은 연구결과가 도출되었다. 스포츠를 통한 사회적 책임활동은 기업능력, 기업평판， 기업신뢰에 정(+)의 영향을 미치는 것으로 나타났으며, 기업능력은 기업평판에 정(+)의 영향을 미치는 것으로 나타났다. 또한 기업능력과 기업신뢰는 기업평판에 정(+)의 영향을 미치는 것으로 나타났고, 기업평판은 고객만족과 구매의도에 그리고 고객만족은 구매의도에 정(+)의 영향을 미치는 것으로 나타났다. 마지막으로 사회적 책임활동과 기업평판의 관계에서 기업능력과 기업신뢰의 매개효과가 나타났고, 기업능력과 기업평판의 관계에서 기업신뢰의 매개효과가 나타났다. 또한 기업평판과 구매의도의 관계에서 고객만족은 매개효과가 나타났다. 결론적으로 스포츠를 통한 사회적 책임활동은 기업요인을 거쳐 고객만족 및 구매의도의 소비자요인에 영향을 미치는 것으로 확인되었다. 이는 기업의 스포츠분야에 대한 사회적 책임활동이 소비자에게는 매우 효과적인 마케팅 수단으로 작용하고 있음을 증명하는 결과이며, 기업능력, 기업신뢰, 기업평판의 기업요소에도 직접적인 영향을 미치는 주요 활동임을 나타내고 있다. The purpose of this study is to analyze the effects of corporate social responsibility through sport on customer factors (customer satisfaction and purchase intent) via corporate factors (corporate trust, corporate capability, and corporate reputation). The subjects of this study were general citizens of 20 and over who resided in G Metropolitan City arid Y City arid S City in J Province and participated in sport for all class. The structural equation model using AMOS 5.0 was applied to statistics processing to derive study results. 276 questionnaires were used for the final analysis. Finally, the following results were drawn. Corporate social responsibility through sport was found to have a positive effect on corporate ability, corporate reputation, corporate trust and corporate ability had a positive effect on corporate reputation. And corporate ability and corporate trust had a positive effect on corporate reputation and corporate reputation had a positive effect on customer satisfaction arid purchase intention and customer satisfaction had a positive effect on purchase intention. Lastly, in the relationship between corporate social responsibility and corporate reputation mediated effect of corporate ability and corporate trust took effect and in the relationship between corporate ability and corporate reputation mediated effect of corporate trust worked. In conclusion, it was confirmed that corporate social responsibility through sport influenced customer factors (customer satisfaction and purchase intent) via corporate factors. It demonstrated that corporate social responsibility in the sport field acted as very effective marketing means to customers and chiefly influenced directly and indirectly corporate evaluation elements of corporate capability, corporate trust, and corporate reputation. Accordingly, corporations will be required to promote and improve a corporate image through developing and applying a variety of social responsibility such as education, culture, support, and community contribution grafted into sport. Moreover, it is necessary to extend the range of social responsibility which is limited to pro sport or popular items arid to actively explore supports for young athletes through raising sport funds.